2005
DOI: 10.1093/carcin/bgi241
|View full text |Cite
|
Sign up to set email alerts
|

An animal model for the rapid induction of tongue neoplasms in human c-Ha- ras proto-oncogene transgenic rats by 4-nitroquinoline 1-oxide: its potential use for preclinical chemoprevention studies

Abstract: Oral squamous cell carcinoma is one of the most common human neoplasms, and prevention of this malignancy requires a better understanding of its carcinogenesis process. To this end, we tried to establish an animal model using the human c-Ha-ras proto-oncogene-carrying transgenic (Tg) rats and the carcinogen 4-nitroquinoline 1-oxide (4-NQO). 4-NQO (20 p.p.m.) was administered to Tg and non-Tg rats for 8 weeks in their drinking water, and then the occurrence of tongue carcinogenesis was compared during the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 57 publications
(62 reference statements)
2
41
2
1
Order By: Relevance
“…These results clearly show that Hras128 rats are more sensitive to 4NQO induced tongue carcinogenesis than SD rats. This susceptibility to a carcinogen is in accordance with previous experiments demonstrating that Hras128 rats are more sensitive to a 7,12-dimethylbenz[a]anthracene (DMBA) or 4NQO in the mammary or tongue tumors than were wild-type SD rats (11,21). In addition, Miyamoto et al demonstrated that the rasH2 mouse carcinogenesis model is highly susceptible to 4NQO induced tongue and esophageal tumors (12).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These results clearly show that Hras128 rats are more sensitive to 4NQO induced tongue carcinogenesis than SD rats. This susceptibility to a carcinogen is in accordance with previous experiments demonstrating that Hras128 rats are more sensitive to a 7,12-dimethylbenz[a]anthracene (DMBA) or 4NQO in the mammary or tongue tumors than were wild-type SD rats (11,21). In addition, Miyamoto et al demonstrated that the rasH2 mouse carcinogenesis model is highly susceptible to 4NQO induced tongue and esophageal tumors (12).…”
Section: Discussionsupporting
confidence: 90%
“…Human oral cancer is a focal disorder (3), and experimental studies have indicated that there is a multistage process in the development of the oral lesions, in which dysplasias process to SCC through PAP (11,12). The results obtained in the present study showing that Hras128 and SD rats developed DH and tumors in a time-dependent manner (Fig.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This has been reported previously and attributed to the intrinsic characteristics of performing DNA ploidy analysis using thin tissue sections. 43,64 Thick tissue sections (e.g., 410 μm) create difficulty in nuclei segmentation, especially in situations of touching and overlapping nuclei. Therefore, biased sampling error could happen where smaller and isolated nuclei are preferred.…”
Section: Discussionmentioning
confidence: 99%